Exploring the risk factors and clustering patterns of periodontitis in patients with different subtypes of diabetes through machine learning and cluster analysis - Anna Zhao; Yuxiang Chen; Haoran Yang; Tingting Chen; Xianqi Rao; Ziliang Li (Acta Odontologica Scandinavica)
Aim: To analyse the risk factors contributing to the prevalence of periodontitis among clusters of patients with diabetes and to examine the clustering patterns of clinical blood biochemical indicators.